Efeito do tratamento térmico na formação de revestimentos GA sobre aços com características de bake hardenability - Aldo Henrique de Almeida Barbosa (2010)
Galvanneling heat treatment exerts a significant influence on the galvannealed coating quality, once it affects the formation of Fe-Zn intermetallic compounds. Small variations on temperature and process time lead to consequences that go from coating malformation, due to the lack of thermal flux, to delamination, due to overheating. The heat treatment influence is more pronounced in high strength steels with P and B, once these elements reduce the substrate reactivity, increasing the necessity of a strict thermal flux control to promote the coating formation and to compensate productivity losses. Thus, a study was proposed to determine the effects of heat treatment conditions on the galvannealed coating formation on high strength steels with fósforo and B, and bake hardenability. For that, a technique for developing galvanneling heat treatment models was established. Galvanneling process simulations were carried out in laboratory scale varying heat treatment temperature from 530°C to 580°C. For all simulations, complete galvannealing cycles (fully processed samples) were produced, as well as, galvannealing cycles interrupted during the soaking stage, by fast cooling of the samples, aiming to evaluate the coating microstructure evolution during the treatment. The coatings characterization was carried out by plasma spectrometry, scanning electron microscopy, Auger spectrometry, electrochemical stripping of zinc layer, X-ray diffraction and electron backscattered diffraction. This study results allowed the determination of the galvannealing conditions effects on the galvannealed coating formation, being possible to establish optimal conditions to the galvanneling heat treatment of high strength steels with fósforo and B. Furthermore, the results also allowed the determination of a correlation between steel and coating microstructure, making possible to establish actions to minimize defects like craters, cracks and delamination. Moreover, the heat treatment and characterization methodologies developed in this study will be applied to evaluate other steels, mainly the ones with high mechanical strength, for which the galvannealing processes were not optimized, bringing remarkable benefits to them.